2016
DOI: 10.1002/ceat.201500743
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Liquid Flow in Microchannels at very Low Reynolds Numbers

Abstract: The flow characteristics of deionized water and kerosene through smooth rectangular microchannels with hydraulic diameters ranging from 5.0μm to 17.4μm are studied experimentally. Through the special design of the experimental setup, the range of the measured average liquid velocity in microchannels can reach 0.001mm/s to 1 mm/s, corresponding to Reynolds number ranges from10 -5 to 10 -2 . The experimental data show that the pressure drop exhibits a linear relationship with the average velocity of the fluid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Hence, researchers have been seeking to fabricate effective microstructure devices that can operate using as low of a pressure drop as possible. Despite its importance, the number of reported studies on liquid–liquid two-phase pressure drop in microchannels has been so far very limited. ,,,,,,,, These studies have observed that the pressure drop is most highly influenced by the flow patterns and the velocity and properties of the fluids, as well as by the size and roughness of the channels used. Before elaborating on the findings of different researchers, note that, to measure the pressure drop of a two-phase system, a differential pressure transducer is usually used.…”
Section: Pressure Dropmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, researchers have been seeking to fabricate effective microstructure devices that can operate using as low of a pressure drop as possible. Despite its importance, the number of reported studies on liquid–liquid two-phase pressure drop in microchannels has been so far very limited. ,,,,,,,, These studies have observed that the pressure drop is most highly influenced by the flow patterns and the velocity and properties of the fluids, as well as by the size and roughness of the channels used. Before elaborating on the findings of different researchers, note that, to measure the pressure drop of a two-phase system, a differential pressure transducer is usually used.…”
Section: Pressure Dropmentioning
confidence: 99%
“…The process in microdevices involves the flow of different fluids in microchannels whose dimensions vary from submicrometers to submillimeters. The flow in the microscale is not subjected to the force of gravity but rather is dependent on the viscous, surface tension, and inertia forces, which results in the formation of laminar flow. The relationship between these forces is presented in the form of dimensionless numbers to allow a better understanding of the interplay phenomena. , These characteristic features of the microchannels result in improved heat and mass exchange rates with a shorter time and a tiny size, compared to those in the traditional contactors. , However, several studies have also noted that the flow in microchannels introduces new confrontations, in terms of the hydrodynamics of the multiphase process. …”
Section: Introductionmentioning
confidence: 99%
“…Many achievements have been obtained regarding investigating flow field and the transition from laminar to turbulent flow in microchannels with micro-PIV. For example, Zhang et al [27] conducted experiments to research flow characteristics of deionized water and kerosene in microchannels with diameters ranging from 50 to 254 μm under very low Reynolds number conditions (105<Re<102). Micro-PIV was applied to measure the velocity distribution inside the microchannels and the result was in strong agreement with the value calculated by the Navier–Stokes equation.…”
Section: Introductionmentioning
confidence: 99%
“…This change in local shear rate at wall leads to slip flow which depends upon the surface energy of the solid-liquid interface and other operational parameters like pressure drop [7], Reynolds No. [8] etc. and also in the thermal properties [9].…”
Section: Introductionmentioning
confidence: 99%